A “Motivation” model of couple support for digital technology use among rural older adults - Ma, Jiaojiao; Cui, Jie; Zhang, Qi (Frontiers in Psychology, 2023)
Although recent research has demonstrated spouse support for technology use among older adults, by treating them as a homogeneous group, it has overlooked differences caused by socio-demographic dimensions in their digital engagement. Following the approach of the grounded theory and interviewing 15 couples in a developing aging region (Wuzhi County, Henan, China), this study paints a fuller picture of couple support for technology adoption among older adults in terms of their psychological motivations by dividing older adults into two categories: technology supports and technology recipients. The resulting concepts of motivation (e.g., social norms, benefit driven, perceptual elements, and value satisfaction), particularly limiting motivational factors (e.g.,individual status) reveal the psychological mechanisms behind this process and are conceptualized as a “motivation” model of couple support for digital technology use among rural older adults. Our study has strong implications for active and healthy aging, as policymakers can stimulate external motivation for technology adoption among older adults by fostering a sense of family responsibility and social ethos that encourages couples to help each other. In addition, local communities as stakeholders can educate older adults about the usefulness, ease of use, and risk-averse means of digital technology, and satisfy their altruistic and egoistic psychological needs to increase the inner value satisfaction they gain from the couple support process. By doing this, motivation and engagement are thereby increased, and ultimately, technology adoption in disadvantaged socioeconomic groups may be improved.